1993
DOI: 10.1016/s0248-4900(05)80177-7
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome through cell differentiation and neoplasia

Abstract: Peroxisomes are essential in cellular metabolism as their dysgenesis or defects in single enzymes or impairment of multiple peroxisomal enzymatic functions have been found in several inherited metabolic diseases with serious clinical sequelae. The assembly and formation of these cytoplasmic organelles constitute a major and intriguing research topic. In the present study the biogenesis of peroxisomes and the developmental patterns of their enzymes have been reviewed during embryonic and/or post-embryonic ontog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 69 publications
4
29
0
Order By: Relevance
“…The content and function of the enzymes within the peroxisome may vary in the different cell types. In environments with competing metabolic needs, the physiological needs of the cellular environment dictate the state of the peroxisome population and peroxisomal protein content (Keller et al, 1993(Keller et al, , 2000. In our previous study we have demonstrated that peroxisomal number and peroxisomal enzymes, mainly those related to lipid metabolism, are strongly upregulated in function of the glioma malignancy grade (Benedetti et al, 2010), in this study we evaluated the expression profiles of several peroxisomal proteins on primary cultures derived from patients affected by glioma at different grades of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The content and function of the enzymes within the peroxisome may vary in the different cell types. In environments with competing metabolic needs, the physiological needs of the cellular environment dictate the state of the peroxisome population and peroxisomal protein content (Keller et al, 1993(Keller et al, , 2000. In our previous study we have demonstrated that peroxisomal number and peroxisomal enzymes, mainly those related to lipid metabolism, are strongly upregulated in function of the glioma malignancy grade (Benedetti et al, 2010), in this study we evaluated the expression profiles of several peroxisomal proteins on primary cultures derived from patients affected by glioma at different grades of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…When their electron density is less opaque, one can also find a straight, twisted, or curved, narrow crystal of catalase (Baumgart et al, 1997). Their apical and near apical location is typical for the bile tract as the same kind of peroxisomes are always found associated with the apices of cells in developing and differentiated bile canaliculi (Keller et al, 1993), bile ducts and in the mammalian gallbladder epithelium (Depreter et al, 2002;Kojima et al, 2003); they are similarly located in the gallbladder of other fish species (Kramar et al, 1974;Ruiter et al, 1985Ruiter et al, , 1988. The peroxisome-mitochondria association is a metabolic requirement in all cells as the peroxisomes offer protection against oxidative species and assist in oxidations of long lipids, while the mitochondria are needed for the oxidative phosphorylation pathways and, in association with peroxisomes, to perform some b-oxidation and other metabolic functions while ''protecting'' the cells against toxic bile acids in this large gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies had suggested that peroxisomes form a homogeneous population without further differences between organs or stages of development. Nevertheless, subsequent cytochemical and ultrastructural analyses showed that in vertebrates the peroxisome undergoes a process of maturation, increasing in size and number and gaining new capabilities along the embryonic development and early infancy (Keller et al, 1993).…”
Section: Introductionmentioning
confidence: 99%